Use of interactive accounting game to enhance students' test scores : evidence from Universiti Teknologi MARA Sarawak / Susana Narawi, Shaft Mohamad and Lulu Jonathan - Narawi, Susana; Mohamad, Shaft; Jonathan, Lulu (Research Management Institute (RMI), 2011)
A strong foundation in the basic principles of accounting is important for accounting students as they move on to further studies in financial accounting of higher levels. The aim ofthis research was to investigate whether there were any significant differences in accounting students' performance after being exposed to the Accounting Balancing Game at Universiti Teknologi MARA (UiTM) Sarawak. This study found that 76% of the accounting students who were exposed to the Accounting Balancing Game improved their performance. The results showed that there was a significant improvement between pre and post-test scores by the experimental group. However there was no significant improvement between pre and post-test scores by the control group. Hence the results of this study offer useful insights in enhancing the teaching and learning of financial accounting for future accounting students in local universities.